2021
DOI: 10.1111/let.12438
|View full text |Cite
|
Sign up to set email alerts
|

Coprolites in natural traps: direct evidence of bone‐eating carnivorans from the Late Miocene Batallones‐3 site, Madrid, Spain

Abstract: We describe two carnivoran coprolites found in the pseudokarst natural carnivore trap of Batallones-3, from the Late Miocene of Spain. The larger one, comprising multiple indistinguishable fragments of broken and corroded bones, indicates that the producer of the dropping might have been highly capable of crushing the softer parts of large bones. On the other hand, the smaller one shows several relatively larger and more complete bone fragments, thus exhibiting a greater capacity to break and swallow large por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…The difficulty of identifying bone inclusions within the PSMP coprolites using µCT to a level beyond generic bone type was not a limitation of µCT itself, but rather a consequence of how much the bones were masticated and digested. Similar results were documented by Abella et al (2022), wherein they solely used µCT, but found many of the bones were not identifiable to a certain anatomical bone or taxon, and instead the authors relied on describing the general shape and features. Studies comparing the results of mechanical extraction and µCT analysis have encountered similar difficulties.…”
Section: Evaluation Of µCt For Analysis Of Psmp Coprolitessupporting
confidence: 68%
See 4 more Smart Citations
“…The difficulty of identifying bone inclusions within the PSMP coprolites using µCT to a level beyond generic bone type was not a limitation of µCT itself, but rather a consequence of how much the bones were masticated and digested. Similar results were documented by Abella et al (2022), wherein they solely used µCT, but found many of the bones were not identifiable to a certain anatomical bone or taxon, and instead the authors relied on describing the general shape and features. Studies comparing the results of mechanical extraction and µCT analysis have encountered similar difficulties.…”
Section: Evaluation Of µCt For Analysis Of Psmp Coprolitessupporting
confidence: 68%
“…Evidence of osteophagy was based on abundant skeletal inclusions including fragments that appeared to belong to larger bones while others display depressions resembling partial tooth marks. Similar to the Class I PSMP coprolites, the larger specimen of the Spanish coprolites (specimen BAT-3′9.178) preserves irregular bone fragments not identifiable to a specific anatomical bone but does show evidence of digestive corrosion (Abella et al, 2022). The smaller coprolite (BAT-3′10.153), which is comparable in length to the PSMP Class I coprolites exhibits more complete skeletal elements and has a greater proportion of bone inclusions relative to the larger coprolite at the same locality (Abella et al, 2022;Figures 4, 6).…”
Section: Insights Into Feeding Behaviormentioning
confidence: 89%
See 3 more Smart Citations